2013
DOI: 10.1111/idj.12037
|View full text |Cite
|
Sign up to set email alerts
|

Carpal tunnel syndrome – an occupational hazard facing dentistry

Abstract: Dentists have an increased risk of carpal tunnel syndrome and precautions and care should be exercised to prevent detrimental irreversible changes occurring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 16 publications
0
14
1
Order By: Relevance
“…Moreover, pipetting involves repeated forceful thumb movement pressing the plungers with repeated hand motion and wrist twisting for prolonged time, and all these movements are risk factors of CTS 9 , 34) . Several studies reported that workplace ergonomic is an important risk factor of work related musculoskeletal disorders, including CTS 7 , 9 , 35) . Based on that, using unadjustable chairs or desk can affect the level of the laboratory technician's elbows in relation to his workstation, causing prolonged wrist flexion or extension which might lead to CTS 5 , 35) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, pipetting involves repeated forceful thumb movement pressing the plungers with repeated hand motion and wrist twisting for prolonged time, and all these movements are risk factors of CTS 9 , 34) . Several studies reported that workplace ergonomic is an important risk factor of work related musculoskeletal disorders, including CTS 7 , 9 , 35) . Based on that, using unadjustable chairs or desk can affect the level of the laboratory technician's elbows in relation to his workstation, causing prolonged wrist flexion or extension which might lead to CTS 5 , 35) .…”
Section: Discussionmentioning
confidence: 99%
“…Carpal tunnel syndrome (CTS) is related to compression and irritation of the median nerve within the carpal tunnel in the wrist, and it is associated with certain risk factors such as diabetes, hypothyroidism, pregnancy, rheumatoid arthritis, and occupational factors 1 - 3) . Various studies have reported that CTS is the most common entrapment neuropathy of the upper extremity in the working populations that is associated with different work-related factors, mainly repetitive movements, forceful manual exertion, frequent twisting of the wrist, and hand-arm vibration 2 , 4 - 7) . Healthcare workers, including laboratory technicians, are at risk for developing upper extremity musculoskeletal disorders, including CTS 8 - 10) .…”
Section: Introductionmentioning
confidence: 99%
“…The most recent study, published in 2005 by Sartorio et al (2005) reported that these disorders occur in 54–93% of dentists, with a higher incidence in older individuals and women. The areas of the body mainly affected by repetitive strain are the shoulders and wrists, which often display symptoms of carpal tunnel syndrome ( Abichandani, Shaikh & Nadiger, 2013 ; Jodalli et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…8 There is an additional requirement for proceeding with dental instruction programs in dentistry so dental technicians can refresh themselves with the most recent and more up to date strategies and materials available. [10][11][12][13] The present study is undertaken to identify different work place related hazards and conditions of dental laboratories among dental technicians in Karachi city.…”
Section: Sohail Saadat 3 Bds Mdsmentioning
confidence: 99%